Why it Is Indeed Time for the Westminster Model to Be Retired from Comparative Politics. Issue 2 (3rd April 2022) - Russell, Meg; Serban, Ruxandra
Abstract: The term 'Westminster model' is frequently used by political scientists and practitioners. But our recent examination (Russell and Serban 2021 ), published in this journal, uncovered wide variation in how it is defined – demonstrating that it is more 'muddle' than 'model'. This sparked a response article from Flinders et al. (2021 ), which we in turn respond to in this piece. We briefly revisit our initial research questions, methodology and findings, before reflecting on their analysis. We emphasize that, notwithstanding the critics' negative tone, we and they agree on certain fundamentals. In particular on our original central point, that the 'Westminster model' is an ill-defined term with a long history, which mostly makes it unsuited to positivist comparative political science research. While the 'Westminster model' may have some valid vestigial uses, within the UK political system, or as an object of study for interpretivist political science, it does not provide a rigorous basis for case selection and comparative political science analysis.